2021
DOI: 10.52963/perr_biruni_v10.n3.06
|View full text |Cite
|
Sign up to set email alerts
|

Competency-Based Education: Theory and Practice

Abstract: This study aimed to reach a pro on Competency-Based Education (CBE) through the opinions of Educational Sciences experts and to review the literature on CBE. In this study, convergent design, one of the mixed methods research, was used, and a semi-structured questionnaire was used to collect data. The sample was selected through convenience sampling and consisted of 28 participants. In the study, the documents related to National and International Qualifications Frameworks, history of CBE, its comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Competence is a combination of knowledge, skills, values and attitudes reflected in thoughts and action (Caena & Redecker, 2019;Ramadani et al, 2022). Furthermore, the Competency-Based Curriculum emphasizes more on the ability/skill to do something related to certain activity (Açikgöz & Babadogan, 2021).…”
Section: Figure 2 Research Variablesmentioning
confidence: 99%
“…Competence is a combination of knowledge, skills, values and attitudes reflected in thoughts and action (Caena & Redecker, 2019;Ramadani et al, 2022). Furthermore, the Competency-Based Curriculum emphasizes more on the ability/skill to do something related to certain activity (Açikgöz & Babadogan, 2021).…”
Section: Figure 2 Research Variablesmentioning
confidence: 99%
“…The study shows that professional and competency issues are considered in terms of research preparation, creativity, innovation etc. When analyzing research on competencybased learning models it was revealed that in terms of ability, the most important thing is the experience of the student and the readiness to set goals (Açıkgöz & Babadoğan, 2021;Nihishova & Kryvonosova, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Implementing competency-based education in health professions education within lowresource settings presents significant challenges. Competency-based education (CBE) is a model for designing and implementing education that focuses on the desired performance characteristics or outcomes of healthcare professionals (1). The CBE model is set to improve student competence by predefining educational outcomes, also known as Entrustable Professional Activities, that support learning and teaching activities (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Implementors of the CBE model must ensure the feasible use of robust assessment methods that result in valid and reliable scores that can be used to provide feedback on learning and make decisions about student progression (6,1). Conventional assessment approaches focus on end-of-course high-stakes examinations of knowledge and may be oblivious to authentic performance (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation